Meningkatan Metakognisi Siswa dalam Pembelajaran Matematika Melalui Asesmen Kinerja Berbasis Masalah dan Model Pembelajaran - Kadir Kadir (Badan Litbang dan Diklat Kementerian Agama RI, 2009)
The study was conducted in SMU in Jakarta. There were 120 first grade students as the sample of the study, selected through multistage random sampling. The data were gathered by using a metacognition scale. Data analysis was done by using the two-way analysis of variance. The results of the study are: (1) In general, problem-based performance assessment effects students’ metacognition in mathematics, (2) Learning models affect the students’ metacognition in mathematics; in which the cooperative learning model is more effective in improving the students’ metacognition than the classical learning model, (3) There is an interaction effect between problem-based performance assessment and instructional models. Such interaction show that problem solving performance assessment is more effective in improving students’ metacognition in mathematics if it is combined with cooperative learning model; while problem posing performance assessment is more effective if it is combined with classical learning model.